2014
DOI: 10.1002/app.41513
|View full text |Cite
|
Sign up to set email alerts
|

A new method to prepare low melting point polyamide‐6 and study crystallization behavior of polyamide‐6/calcium chloride complex by rheological method

Abstract: A new method to prepare low melting point polyamide-6 (LPA6) by complex reaction of calcium chloride (CaCl 2 ) and polyamide-6 (PA6) in a co-rotating twin screw extruder was reported. We employed a new rheological method to study the crystallization behavior of PA6/CaCl 2 complex and the mechanism of confined crystallization of PA6. Compared with differential scanning calorimetry (DSC), this method was more capable of detecting crystalline information. What's more, it was also an effective method for studying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…To further verify the successful preparation of CaCl 2 -PA-66 and quantify the IC(CaCl 2 ) values of these ionenes, the Ca contents of 2.0 wt% CaCl 2 -PA-66, 5.0 wt% CaCl 2 -PA-66 and 10.0 wt% CaCl 2 -PA-66 relative to PA-66 were measured by ICP-OES. Based on the above FTIR spectra, two assumptions were made in the quantitative IC calculations: each CaCl 2 molecule is complexed with the two carbonyl O atoms from any two amide groups of PA-66; 26 and both amide groups of any participating structural repeat unit are ionised to form an ionised structural repeat unit. Hence, the IC(CaCl 2 ) values of the four samples were counted by eqn (1), and the resulting data are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…To further verify the successful preparation of CaCl 2 -PA-66 and quantify the IC(CaCl 2 ) values of these ionenes, the Ca contents of 2.0 wt% CaCl 2 -PA-66, 5.0 wt% CaCl 2 -PA-66 and 10.0 wt% CaCl 2 -PA-66 relative to PA-66 were measured by ICP-OES. Based on the above FTIR spectra, two assumptions were made in the quantitative IC calculations: each CaCl 2 molecule is complexed with the two carbonyl O atoms from any two amide groups of PA-66; 26 and both amide groups of any participating structural repeat unit are ionised to form an ionised structural repeat unit. Hence, the IC(CaCl 2 ) values of the four samples were counted by eqn (1), and the resulting data are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…24 Some studies on polyamide materials modified by Ca 2+ also revealed the complexation of amide group with Ca 2+ . [25][26][27] These findings can make surfactants containing polyoxyethylene group and amide group replace chelating agents in detergents to prevent water pollution and achieve sustainability.…”
Section: Introductionmentioning
confidence: 99%